INTELLIGENT SPEECH RECOGNITION AND VOICE OPERATED ROBOT WITH WIRELESS VOICE & VIDEO TRANSMISSION TO REMOTE TELEVISION (International Journal of Food and Nutritional Sciences, 2021)
Spoken recognition is an approach that converts spoken input into text without the need for a speaker. This means that it may be used for a variety of tasks, including as operating machines and acting as a digital assistant. This research proposes a networked voice input approach for robotic vehicle control. The speech recognition platform will be an Android smartphone that connects to the robot using Bluetooth. This technique enables efficient identification and smooth data transfer. In addition, the robot will be able to identify obstacles and notify the user when a new command is required. Our proposed approach will be beneficial for both assistive robots for people with impairments and industrial applications such as labour robots